SURVEY STUDY OF THE DRUGSTORE CLUB MEMBERS’ PERCEPTION AND ADAPTATION OF THE MINISTERIAL REGULATIONS: THE APPLICATION FOR AND GRANT OF A LICENSE TO SELL MODERN DRUGS B.E. 2556. - Chalongsuk, Rapeepun; Limsupjaroen, Kamonwan; Rattananil, Ponsiri; Sritrakul, Worakamon; Ratri, Watthana (Thai Bulletin of Pharmaceutical Sciences, 2018)
Since June 25, 2014, when the Ministerial Regulations: THE APPLICATION FOR AND GRANT OF A LICENCE TO SELL MODERN DRUGS B.E. 2556. (MR 2556) was implemented; all drugstores in Thailand have been affected. The purpose of this descriptive study was to survey the perception and adaptation of the members of the Drugstore Club of Thailand toward MR 2556. 1,254 questionnaires were mailed to entrepreneurs who were members of the Drugstore Club between January 20, 2017 and February 14, 2017. Descriptive statistics were used to analyze the data received. The results showed that 48.2% of the respondents were pharmacists but only 13.8% of these entrepreneurs performed as pharmacists who received pharmacy permit and 46.4% performed as pharmacists in charge pharmacists. The monthly revenue from pharmacy was between 2,500 and 456,000 Baht (for a type 1 drugstore) and between 2,000 and 200,000 baht (for a type 2 drugstore). Most of the sample group (94.8%) were perceived of MR 2556 and 90.4% knew about the enforcement date, but were unclear about some legal details regarding the regulations. More than 60% of the entrepreneurs were legally able to practice under the regulations. Those who could not practice under MR 2556 were likely to go out of business.